Mi gran boda griega - Zwick, Joel (Madrid Dolby, 2002)
A young Greek woman falls in love with a non-Greek and struggles to get her family to accept him while she comes to terms with her heritage and cultural identity.
Nia Vardalos, John Corbett, Michael Constantine
Para todos los públicos
Idiomas : Inglés y castellano. Subt.: inglés y castellano
Keywords: Películas cinematográficas -- DVD